Angiosperm fossil woods from the Upper Cretaceous of Western Antarctica (Santa Marta Formation) - Pujana, Roberto Roman; Iglesias, Ari; Raffi, María Eugenia; Olivero, Eduardo Bernardo (Cretaceous Research)
We identified six fossil-species of angiosperms based on fossil woods from two small collections from the Beta Member (lower Campanian) of the Santa Marta Formation on James Ross Island: 1) Paraphyllanthoxylon antarcticum sp. nov., a new species of Paraphyllanthoxylon (Angiosperm incertae sedis) which represents the first Antarctic record of that fossil-genus; three previously known Antarctic fossil-species, but from new localities, 2) Laurelites jamesrossii (Laurales), 3) Hedycaryoxylon tambourissoides (Monimiaceae) and 4) Eucryphiaceoxylon eucryphioides (Cunoniaceae); 5) Weinmannioxylon trichospermoides sp. nov., a new species of Weinmannioxylon (Cunoniaceae); 6) and Cretaceoxylon heteropunctatum gen. et sp. nov., a new fossil-genus and fossil-species with uncertain affinity, but with similar wood anatomy and vessel-ray parenchyma pits to the Santalales and Malpighiales. The richness of angiosperm woody species is increased for the Late Cretaceous of Antarctica. The fossil woods are used to interpret ancient forests composition and to make some climatic inferences during the Campanian of the Antarctic Peninsula. Fil: Pujana, Roberto Roman. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina Fil: Iglesias, Ari. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Instituto de Investigaciones en Biodiversidad y Medioambiente. Universidad Nacional del Comahue. Centro Regional Universidad Bariloche. Instituto de Investigaciones en Biodiversidad y Medioambiente; Argentina Fil: Raffi, María Eugenia. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Universidad Nacional de Tierra del Fuego. Instituto de Ciencias Polares, Recursos Naturales y Ambiente; Argentina Fil: Olivero, Eduardo Bernardo. Consejo Nacional de Investigaciones Científicas y ...